INDIA’S PARTICIPATION IN THE REGIONAL TRADE AGREEMENTS - V. I. Baronov; G. M. Kostyunina (Vestnik MGIMO-Universiteta, 2017)
The main objective of the proposed study is to identify the specifics of India’s participation in the regional trade agreements (RTAs), a comparative analysis of the main provisions of the RTAs and the impact of membership in the integration agreements on the country’s foreign trade relations. In the world economic literature there is no unity of opinions on the economic effect of the participation of states in RTAs. The author’s thesis is that the final effect of membership in the RTAs depends on the amount of customs duties on the date of signing the agreement (the higher they are, the greater the effect of trade creation), and also on the place of the partner country in the trade of another participating state (the greater is mutual turnover, the greater effect of trade creation). Of course, other factors affect, such as geographical proximity, transportation and other transaction costs. India’s participation in the regional trade agreements (RTA) was one of the tasks of implementing the policy “Look East”, which was approved in 1991. The countries of Southeast Asia have been identified as a regional priority, which was caused by the geo-strategic and economic reasons. Later, regional coverage has been extended to the countries of Northeast and South Asia because of increasing the role of China in the world economy and politics, which has become a strategic challenge and economic opportunities for the Indian economy. India is a participant of 13 RTAs, the majority of which are bilateral. In India’s integration practice, one of four types of RTAs is applied: (1) agreement on comprehensive economic partnership, which differ in the widest scope of mutual economic relations; (2) agreement on comprehensive economic cooperation; (3) free trade agreement; (4) preferential trade agreement. Most often, there is used classical integration model (of preferential or free trade area).Initially, the Indian policy of RTA dominated the political factor (taking into account the geographical proximity of the States), subsequently economic factor became the prevalent one. Most of the regional trade agreements, especially with developed countries (Japan, Republic of Korea and Singapore) entail trade diversion effect for India, which is particularly reflected in the reduction of the share of the RTA’s member countries in the Indian exports from 45.1% to 41.3% in 2005-2015. The growth rates of India’s exports to the partner states less than that for imports from RTAs members. At the same time, the effect of trade creation provide agreements with less developed countries as Sri Lanka, Afghanistan, and Nepal. Lessons from the Indian practice of the RTA’s membership include: (1) the need for a more careful approach to choosing a potential partner; (2) the importance of a broad scope of issues of liberalization of mutual economic relations in order to obtain larger economic benefits for the Indian economy. The results of this study will contribute not only to acquaintance with the history and tendencies of India’s participation in RTAs, but also to a further deeper understanding of this form of cooperation of not only in India but also in the other states.